STUDI FITOPLANKTON DI KOLAM KEBUN RAYA BOGOR - I NYOMAN K. KABINAWA (BERITA BIOLOGI, 1989)
I NYOMAN K. KABINAWA, 1989. Study ophytoplankton in Bogor Botanical Garden Ponds Berita Biologi 3(9): 467 - 469. An investigation was carried out in the Bogor Botanical Garden ponds from February 1983- January 1984 to study the diversity,structure and abundance of phytoplanktons.The samples were collected twice a day: in the morning (07.00) and in the afternoon (12.30),twice a week. Among 85 species of phytoplanton observed, Merismopedia punctata, Oiroococcus indicus, Oscillatoria sp.(Cyanophyceae), Scenedesmus quadricaudata, Chlorococcus sp.(Chlorophyceae), and Melosira granula (Bacillariophyceae) were the most common species.Cyanophyceae is the most common group of phytoplankton with the population of 0.680 - 2.80 million cells/1 followed by Chlorophyceae and Bacillariophyceae with the total population of 0.32 - 0.60 and 0.28 - 0.60 million cells/1 respectively. In contrast, the population of Euglenophyceae was only 13,000 cells/1 and Dinophyceae 0 (nil - 120,000 cells/1.Hydrological conditions of water of the Bogor Botanical Garden ponds were good for aqualitic organisms and may belong to the eutrophy water.